Tindak Tutur Lokusi Anak dalam Video YouTube ODG: “Are You A Rich Kid?” Kids Answer - Isnaeny Aplia Sutiarto; Rastya Ismatriyana; Hima R.D.P. Mahendra; Jayanti Megasari (JLA (Jurnal Lingua Applicata), 2021)
This research is a pragmatic research with the discussion of Korean speech acts. The object of this research is the speech of children aged 14 years in the video "Are You a Rich Kid?" Kids Answer from the ODG YouTube channel. This research aims to identify locutionary speech acts uttered by speakers and to determine the purpose of those utterances. In the video there is an interview between staff and children with the topic about the terms “Golden Spoon” and “Dirty Spoon”. The term is used to indicate a person's social class in society. This research uses a qualitative-descriptive method. In data collection, listening and taking notes were used as research techniques. The theory used as the basis of this research is Austin's speech act theory. Also, based on Anggraini's opinion, who divides locutionary speech acts into three, namely: (1) statement (declarative), (2) question (interrogative), and (3) command (imperative). This research focuses on declarative locutionary speech acts. From the results of the study, there were 16 declarative locutionary speech acts uttered by children aged 14 years. They already know and understand those terms and then express their opinion. The speakers also clearly state their social class in society.